Seed performance of striped catfish Pangasianodon hypophthalmus Sauvage, 1878 and pasupati (Pangasius sp.) with different stocking density on the nursery recirculation system - Jadmiko Darmawan; Evi Tahapari; Wahyu Pamungkas (Jurnal Iktiologi Indonesia, 2016)
The increasing demand for striped catfish and pasupati seed will be met through an intensive hatchery with a recirculation system and increased stock density. The purpose of this research was to figure out the effect of stocking density on the performance of growth and survival rate of striped catfish and pasupati in the nursery recirculation system. Rearing was carried out on the fiber with a capacity of 30 liters and equipped with aeration installation and recirculation systems. The study was conducted with three stocking density treatments, namely A) 1 fish L-1 , B) 5 fish L-1 , and C) 10 fish L-1 . We used juveniles of striped catfish and pasupati aged 28 days with an average standard length of 2.14 ± 0.31 cm and 2.22 ± 0.25 cm, and total length of 2.63 ± 0.39 cm and 2.75 ± 0.29 cm, and weight of 0.14 ± 0.06 g and 0.16 ± 0.04 g, respectively. The fish were fed thrice a day at satiation level with floating pellet with 30% crude protein content. The result showed that the optimum stocking density for striped catfish was 5 fish L-1 . During this treatment, the survival rate of of striped catfish was 92.33% with specific growth rate of the weight, standard length and total length of fish for 45 days of rearing were 7.85%, 2.42% and 2.40% , respectively. However, an optimum stocking density for pasupati was 1 fish L-1 . The survival rate of pasupati was 71.67% with specific growth rate of weight, standard length and the total length for 45 days of rearing were 10.78%, 3.35% and 3.32%, respectively. Abstrak Permintaan benih ikan patin siam dan pasupati yang terus meningkat akan dapat terpenuhi melalui pembenihan secara intensif dengan sistem resirkulasi dan peningkatan padat penebaran. Tujuan penelitian ini adalah mempelajari pengaruh padat penebaran terhadap performa pertumbuhan dan tingkat sintasan benih ikan patin siam dan pasupati pada pende- deran sistem resirkulasi. Kegiatan pendederan dilakukan pada bak fiber kapasitas 30 liter yang dilengkapi dengan insta- lasi aerasi dan sistem resirkulasi. Penelitian dilakukan dengan tiga perlakuan padat penebaran, yaitu A) 1 ekor L-1 , B) 5 ekor L-1 , dan C) 10 ekor L-1 . Ikan uji yang digunakan adalah benih ikan patin siam dan pasupati berumur 28 hari dengan rata-rata panjang baku 2,14±0,31 cm dan 2,22±0,25 cm, panjang total 2,63±0,39 cm dan 2,75±0,29 cm, serta bobot 0,14±0,06 g dan 0,16±0,04 g. Pakan diberikan secara at satiation berupa pelet terapung dengan kandungan protein ka- sar 30% dan frekuensi pemberian pakan sebanyak tiga kali sehari. Hasil penelitian pada ikan patin siam menunjukkan bahwa padat penebaran optimum ditunjukkan oleh perlakuan 5 ekor L-1 dengan laju pertumbuhan spesifik terhadap bo- bot, panjang baku, panjang total selama 45 hari pemeliharaan sebesar 7,85%, 2,42% dan 2,40%, dengan tingkat sintasan sebesar 92,33%. Hasil penelitian pada ikan patin pasupati menunjukkan bahwa padat penebaran optimum ditunjukkan oleh perlakuan 1 ekor L-1 dengan laju pertumbuhan spesifik terhadap bobot, panjang baku dan panjang total selama 45 hari pemeliharaan sebesar 10,78%, 3,35% dan 3,32%, dengan tingkat sintasan sebesar 71,67%.